A modified higher order zigzag theory for response analysis of doubly curved cross-ply laminated composite shells. Issue 26 (26th October 2022) - Roy, Soumen; Nath Thakur, Sandipan; Ray, Chaitali
Abstract: The present theory deals with static and free vibration analyses based on higher order zigzag theory for laminated composite shells. The finite element shell model is developed considering the thickness coordinate to radius ratio ( z / R ) using nine noded isoparametric quadratic element. The proposed formulation satisfies the interlaminar stress continuity at the interface of laminae and zero shear boundary conditions at free surfaces. The response results obtained by the proposed formulations are compared with the published results. Moreover, new responses results of hyperbolic paraboloidal laminated shells are obtained using the present laminated shell theory and illustrated in the present study.